Habib Husein Ja’far Al Hadar’s Role in Establishing Moderate Islam in The Millenial Generation: The Study Of Foundations and Celengan Pemuda Tersesat - Mursalat (Journal of Asian Wisdom and Islamic Behavior, 2024)
The name Habib Husein Ja’far Al Hadar must be familiar to some millennials. Understandably, not only preaching from assemblies to assemblies, the young Habib also spread the values of love, nationalism, and tolerance through digital media. Besides being very diligent in writing, Habib Ja’far is a content creator. Therefore, the author is interested in discussing how Habib Ja’far in grounding Moderate Islam among the millennial generation? And how the youth foundation philanthropic movement went astray. In this study, the source of the Youtube channel, Pemuda Tersesat, Jedal Nulis, was enriched with literature used as a reference, such as journals, books and research reports. The result of this research is that Habib Ja’far is able to ground moderate Islam among the youngergeneration with his typical millennial appearance with T-shirts and sneakers. In preaching, he also uses digital platforms, through Youtube, Instagram, Facebook and Twitter. Through the YouTube channel Jeda Nulis, and youths are lost, Habib Ja’far packs his da’wah to be more relaxed so that it is easily accepted. Especially during a pandemic like this, many lost youths are struggling economically. Especially those whose livelihood is from selling.